The Brainstorming of Teaching Pragmatics Issues in EFLTIN (Universitas Negeri Semarang, 2022)
Pragmatic competence is an important factor in determining communication success. In reallife interactions, a language learner is expected not only to use language and produce understandable or grammatically correct utterances but also to produce socio-cultural appropriate utterances. However, for students learning English as a Foreign Language (EFL), pragmatic competence, which can be acquired naturally through social interaction, is quite difficult to acquire due to the limited, if not non-existent, use of English to achieve a communication goal in an authentic social interaction/setting. This study is to identify some of the challenges associated with teaching pragmatics at ELTL in Indonesia (henceforth, EFLTIN), as well as to investigate potential solutions based on the concepts and methodologies informed by previous research. A descriptive qualitative research is chosen in this study to identify and to investigate the processing data and research findings. The utilization of authentic materials, input and production activities, as well as clear feedback, are mentioned as some of the strategies to fill gaps in EFL learners' pragmatic knowledge.